2021
DOI: 10.3390/children8050382
|View full text |Cite
|
Sign up to set email alerts
|

Does Dental Fear in Children Predict Untreated Dental Caries? An Analytical Cross-Sectional Study

Abstract: Despite free health care services in Saudi Arabia, the prevalence of caries in children is substantially greater in comparison to other high-income countries. Dental fear in children may be an important issue that needs attention. Therefore, the aim was to investigate the role of dental fear in predicting untreated dental caries in schoolchildren. This analytical cross-sectional study included children aged 8–10 years residing in Saudi Arabia. Dental status via oral examinations was surveyed with the WHO stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…A significant association was found between high DFA and poor oral health-related quality of life (OHRQoL), a multidimensional measure evaluating oral health status and its related functional and psychosocial impacts [ 87 ], in children [ 88 , 89 , 90 , 91 , 92 ] as well as adults [ 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. Significant relationships were also reported between high levels of DFA and measures of poor oral health (e.g., caries experience, gingival health, and toothbrushing frequency) in children [ 3 , 5 , 6 , 7 , 17 , 50 , 51 , 53 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ] and adults [ 4 , 61 , 65 , 66 , 93 ,…”
Section: Resultsmentioning
confidence: 99%
“…A significant association was found between high DFA and poor oral health-related quality of life (OHRQoL), a multidimensional measure evaluating oral health status and its related functional and psychosocial impacts [ 87 ], in children [ 88 , 89 , 90 , 91 , 92 ] as well as adults [ 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. Significant relationships were also reported between high levels of DFA and measures of poor oral health (e.g., caries experience, gingival health, and toothbrushing frequency) in children [ 3 , 5 , 6 , 7 , 17 , 50 , 51 , 53 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ] and adults [ 4 , 61 , 65 , 66 , 93 ,…”
Section: Resultsmentioning
confidence: 99%
“…Dental caries is one of the commonest and perhaps most prevalent diseases affecting the oral cavity [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. It is a microbial disease of the calcified tissues of the teeth, characterized by demineralization of the inorganic component and destruction of the organic content of the tooth [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports from Italy and Australia indicated unequal distributions in caries prevalence among preschoolers. Both studies reported a higher caries prevalence, and they postulated that the severity of caries in preschool children depends on ethnic and immigration groups [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fear is one of the main reasons to avoid dental treatment and to postpone dental care. In this context, children with elevated emotive reactions present a lack of adaptation to situations of anxiety, such as dental attention [27].…”
Section: Discussionmentioning
confidence: 99%